A Prospective Study of Training Methods for Two-Year-Old Thoroughbred Racehorses in Queensland, Australia, and Analysis of the Differences in Training Methods between Trainers of Varying Stable Sizes - Kylie L. Crawford; Anna Finnane; Ristan M. Greer; Clive J. C. Phillips; Emma L. Bishop; Solomon M. Woldeyohannes; Nigel R. Perkins; Benjamin J. Ahern (Animals, 2021)
Worldwide, musculoskeletal injuries remain a major problem for the Thoroughbred racing industry. There is a strong interest in developing training and management strategies to reduce the impact of musculoskeletal injuries, however, progress has been limited by studies reporting conflicting findings, and a limited understanding of the role of different training methods in preventing injury. There is little data on patterns of rest periods and exercise data and how these vary between trainers. This prospective study of two-year-old racehorses was conducted in Queensland, Australia and involved weekly personal structured interviews with 26 trainers over 56 weeks. Detailed daily exercise data for 535 horses providing 1258 training preparations and 7512 weeks at risk were collected. Trainers were categorised into three groups by the mean number of two-year-old horses that they had in work each week over the study duration: (1) Small stables with five or less, (2) Medium stables with 6 to 15 and (3) Large stables with greater than 15 horses in training. Differences between trainers with small, medium and large stable sizes were evaluated using linear regression, Kruskal–Wallis equality-of-populations rank test if linear models were mis-specified or Chi-squared tests for categorical variables. Significant differences were observed between trainers, with horses from larger stables accumulating a greater high-speed exercise volume (p < 0.001), attaining training milestones more frequently (p = 0.01) and taking less time to reach their training milestones (p = 0.001). This study provides detailed data to which training practices from other locations can be compared. Presenting actual training data rather than trainers’ estimation of a typical program provides a more accurate assessment of training practices. Understanding how training practices vary between regions improves comparability of studies investigating risk factors and is an important step towards reducing the impact of musculoskeletal injuries.